2005
DOI: 10.1002/cne.20800
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal architecture of the mosquito deutocerebrum

Abstract: Mosquito behavior is heavily dependent on olfactory and mechanosensory cues, which are detected by receptor neurons on the antenna and on the palps. Recent progress in mosquito sensory genomics highlights the need for an up-to-date understanding of the neural architecture of the mosquito brain. Here we present a detailed description of the neural structure of the primary target of the majority of these neurons, the deutocerebrum, in the African malaria (Anopheles gambiae) and yellow fever (Aedes aegypti) mosqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
184
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(195 citation statements)
references
References 95 publications
(167 reference statements)
10
184
1
Order By: Relevance
“…For example, oral infection by oncogenic HPV types strongly elevated risk for oropharyngeal cancer (OR 230, 95% CI, 44-1200), after adjustment for alcohol and tobacco in a study conducted in Sweden. 101,102 Furthermore, HPV16 seropositivity conferred an estimated 14-fold increase in risk for subsequent oropharyngeal cancer in a nested, case-control study that provided important evidence that exposure preceded development of disease. 99 Although evidence suggests that HPV is associated with cancers in nonsmokers and nondrinkers, 89 the degree to which oral HPV infection may combine with tobacco use or alcohol use or both to increase risk of oral cancer is currently unclear, with some studies suggesting a synergistic effect with tobacco 92 or alcohol, 97 while others have found no such synergy.…”
Section: 100-102mentioning
confidence: 99%
“…For example, oral infection by oncogenic HPV types strongly elevated risk for oropharyngeal cancer (OR 230, 95% CI, 44-1200), after adjustment for alcohol and tobacco in a study conducted in Sweden. 101,102 Furthermore, HPV16 seropositivity conferred an estimated 14-fold increase in risk for subsequent oropharyngeal cancer in a nested, case-control study that provided important evidence that exposure preceded development of disease. 99 Although evidence suggests that HPV is associated with cancers in nonsmokers and nondrinkers, 89 the degree to which oral HPV infection may combine with tobacco use or alcohol use or both to increase risk of oral cancer is currently unclear, with some studies suggesting a synergistic effect with tobacco 92 or alcohol, 97 while others have found no such synergy.…”
Section: 100-102mentioning
confidence: 99%
“…This may explain the lack of macroglomeruli in tick olfactory lobes. The absence of increased glomeruli was also observed in A. aegypti (IGNELL et al, 2005) and R. prolixus (BARROZO et al, 2009). …”
Section: Discussionmentioning
confidence: 65%
“…Assuming that the number of olfactory receptors in A. americanum is similar to that observed in A. variegatum, and considering we counted 16 to 21 glomeruli, it can be hypothesized that each glomerulus is innervated by approximately four afferent neurons. This number is considerably lower than that observed in insects (ANTON & HOMBERG, 1999;IGNELL et al, 2005), but higher than that observed in the predatory mite P. persimilis in which the number of sensory receptor neurons is the same as the number of glomeruli ( VAN WIJK et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations